(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2025)
Rencesione di Pierliugi Pellini, Tre grandi critici. Luigi Blasucci, Remo Ceserani, Francesco Orlando. Siké, 2023.